2022
DOI: 10.1111/jfpe.13998
|View full text |Cite
|
Sign up to set email alerts
|

A Vision Transformer network SeedViT for classification of maize seeds

Abstract: Maize is a crop that is widely cultivated all over the world. Thus, the classification of maize seeds quality is important, while the traditional methods based on the texture, shape, and color which require repeated work is not efficient. Recently, deep learning reached the goal in the field of image processing, and a deep convolutional neural network (DCNN) is often used to do the image classification task. Here, we explored another neural network called Vision Transformer (ViT), which originally was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The model achieved an accuracy of 83% with 77% precision, 76% recall, and 77% F1-score. In [47], the authors modified the classical ViT and proposed SeedViT for the classification of maize seed quality. They used a custom dataset.…”
Section: Vits For Image Classificationmentioning
confidence: 99%
“…The model achieved an accuracy of 83% with 77% precision, 76% recall, and 77% F1-score. In [47], the authors modified the classical ViT and proposed SeedViT for the classification of maize seed quality. They used a custom dataset.…”
Section: Vits For Image Classificationmentioning
confidence: 99%
“…To address this, researchers have employed self-built or enhanced classification networks using RGB images or MSI of the same crop seeds to identify and screen damaged or imperfect seeds. For instance, five different CNN models [23], an improved VGG model [24], a self-built CNN [25], and an enhanced ResNet model [26] were utilized to identify damaged and imperfect seeds of rice, corn, and wheat, respectively. The classification network effectively screened seed phenotypes during breeding activities.…”
Section: Seed Screening and Identificationmentioning
confidence: 99%
“…[11] It has been shown that morphological characteristics are more effective than color characteristics in wheat varieties classification. As seen in Table 1, wheat, [12][13][14][15][16] soybean, [17][18][19] rice, [20][21][22][23][24] weed, [9] corn, [25][26][27] and classification of seeds belonging to different plants [10,28] were studied with high classification accuracy. Olgun et al [13] proposed an automated system for wheat grain classification.…”
Section: Related Workmentioning
confidence: 99%